Intervention in social skills with a child with Down’s Syndrome - Rodrigues, Olga Maria Piazentin Rolim (2014)
Studies show that children with Down’s syndrome have deficits in social skills, which can interfere in their social interactions and also in their academic performance. The aim of this study was to analyze the clinical significance and reliable change in repertory of social skills of a child with Down’s syndrome, from interventions in the clinic, at home and at school. A seven year old girl with Down’s Syndrome who had frequented the first year of regular school, her parents and her teacher participated in this study. They were attending in a Center of Applied Psychology, of a public university in São Paulo State. Before and after the intervention parents and teacher answered the Rating System Social Skills (SSRS). The intervention with the child had been conducted for six months, through playful activities in weekly meetings. It was discussed various topics related to social skills with parents and teacher in biweekly and monthly meetings. The results were analyzed using JT method. With parents, comparing the two assessments conducted, the data pointed to positive change reliable for four of the six skills assessed. Of the five skills assessed by the teacher, one of them was not in the clinical level since the first application. The other two went from clinical to non-clinical level, featuring reliable positive change. The study showed the importance of pre and post measures in case study, enabling the assessment of the effects of the intervention performed on the various factors of social skills. Further studies with larger populations may ratify the data obtained.